Analysis of the Impact of Construction of the Trans Sumatra Toll Road in Order to Encourage the Proud to Travel Program in Indonesia (BBWI) - Wardani, Sri; Sahid, Radiah; Kirana, Fidelia (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This paper describes that toll roads are National Strategic Projects (PSN) that are prioritized by the government to improve accessibility and encourage economic growth in a region. Sumatra Island as the second largest island in Indonesia has a variety of natural, commodity and tourism potential. This policy paper outlines an analysis of the impact of the Trans Sumatra Toll road development on the government's Proud to Travel in Indonesia (BBWI) program. The tourism potential of Sumatra Island is not inferior to that of Java Island. It's just that the island's tourist destinations have limited travel distance, few accommodations and lack of promotion. Thus, Sumatran tourists prefer to visit abroad because it is easier, faster and more affordable. The purpose of this policy paper is to explain the results of the analysis of the Trans Sumatra Toll Road that its existence can improve regional tourism and encourage the WWBI program through tourism management strategies in each province on the island of Sumatra. With a qualitative method approach, this policy paper emphasizes data analysis methods through literature studies from various information both books, journals and official government websites, then the results are assembled by providing informational narratives and policy suggestions. Broadly speaking, the results of this policy paper analysis show that the Trans Sumatra toll road provides benefits to accelerate the distribution of goods and services and has a positive impact on tourist visits in the region. The alternative policy to support the BBWI program is to implement city branding for tourist areas on the island of Sumatra, so that tourism promotion increases tourist visits.